2004
DOI: 10.1023/b:viru.0000032787.77837.09
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Recombination of Hepatitis B Virus Genotype B with Pre-C/C Region of Genotype C

Abstract: Among hepatitis B virus (HBV) genotypes the B and C are most prevalent in China. To further study on the inside story of the intertypes, the genotype of 136 sequences from Chinese patients were analyzed either by restriction fragment length polymorphism on fragments or by phylogenetic analysis and bootscanning on full genome. The 22 complete sequences of genotype B clustered with different genotypes depending on gene fragments analyzed, which indicated that recombinant events occurred during HBV evolutionary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…Dual HBV infection and genomic recombination between different genotypes have been increasingly documented (Simmonds & Midgley, 2005;Sugauchi et al, 2003;Yang et al, 2007). Recombination has been found to occur more frequently in certain 'hot-spot' regions of the viral genome, such as the core region (Bowyer & Sim, 2000;Garmiri et al, 2009;Luo et al, 2004), pre-S1 (Chen et al, 2004), pre-S2/S (Chen et al, 2006;Wang et al, 2005), polymerase (Kurbanov et al, 2005;Magiorkinis et al, 2005) and X (Martin et al, 2011), and has been considered a significant source of HBV genetic variability (Simmonds & Midgley, 2005). In our study, all but one G/F recombinant clones had recombination breakpoints in the core region ( Fig.…”
mentioning
confidence: 99%
“…Dual HBV infection and genomic recombination between different genotypes have been increasingly documented (Simmonds & Midgley, 2005;Sugauchi et al, 2003;Yang et al, 2007). Recombination has been found to occur more frequently in certain 'hot-spot' regions of the viral genome, such as the core region (Bowyer & Sim, 2000;Garmiri et al, 2009;Luo et al, 2004), pre-S1 (Chen et al, 2004), pre-S2/S (Chen et al, 2006;Wang et al, 2005), polymerase (Kurbanov et al, 2005;Magiorkinis et al, 2005) and X (Martin et al, 2011), and has been considered a significant source of HBV genetic variability (Simmonds & Midgley, 2005). In our study, all but one G/F recombinant clones had recombination breakpoints in the core region ( Fig.…”
mentioning
confidence: 99%
“…CCC at nucleotides 1856 to 1858 is found predominantly in HBV genotypes A, C, and F; and CCT at nucleotides 1856 to 1858 is found predominantly in HBV genotypes B, C, D, and E (2,19,20). In contrast, TCC at nucleotides 1856 to 1858 has been reported only in HBV genotype C isolates from Hong Kong, Guangzhou, and Vietnam (13,20,24,28). In our study, it was found almost exclusively within the Cs subgroup of genotype C HBV.…”
Section: Discussionmentioning
confidence: 83%
“…This deletion mutant has previously been reported in different clinical conditions, especially hepatocellular carcinoma (HCC) and chronic hepatitis B (CHB) infection with genotypes C and D, and fulminant hepatitis B (FHB) with genotype A in Africa. It has also been observed in isolates obtained from nonhuman primates (Table 2) [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . Interestingly, there are no reports of this deletion mutation in genotypes B, E, F and G. In a heart transplant recipient who died from fulminate hepatitis B transmitted by the donor, the 18bp deletion was detected in the recipient, but not in the donor [20] .…”
Section: Discussionmentioning
confidence: 99%